THE CONCEPT OF IDEAL PAI TEACHERS ACCORDING TO AL-GHAZÂLÎ AND IT’S RELEVANCE TO PAI TEACHERS IN CONTEMPORARY ISLAMIC EDUCATION - Syahrizal, Syahrizal (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2021)
Abstract: This study described the PAI teachers in contemporary Islamic education based on al-Ghazâlî’s concept, including theirtasks, roles, requirements, relevance, and competency. Followingthe descriptive, textual, and reflective analysis of the Ihyâ’ ‘Ulûm al-Dîn,PAI teachers areexpected to guide the education process, including the aspects of khuluqiyah, ‘ubûdiyah, tauhîdiyah, and tazkiyat al-nafs as stated by al-Ghazâlî. Theyplay essential roles in the student’s success, such as being fathers, mentors, advisors, reformers, psychologists, motivators, demonstrators and evaluators. According to al-Ghazâlî, PAI teachers should be qualified especially in psychology and didactic pedagogy, and be competent in personal and professional religion. Al-Ghazâlî’s concept on the PAI teacher’s tasks, roles, requirements, and competency, is relevant in contemporary Islamic education.Keywords: PAI teachers, al-Ghazâlî, Ihyâ’ ‘Ulûm al-Dîn